THE EFFECTIVENESS OF PBL MODEL TO IMPROVE STUDENTS' LEARNING OUTCOMES AT SMA NEGERI 2 SALATIGA - Dwi Ratnasari; Arief Yulianto; Fahrur Rozi (Universitas Negeri Semarang, 2025)
The Problem-Based Learning (PBL) model is recognized as an effective instructional approach that enhances both the learning process and student outcomes. It actively engages students in identifying, analyzing, and solving real-world problems, thereby fostering critical thinking, problem-solving, and collaboration skills. In school settings, PBL significantly improves conceptual understanding, knowledge retention, and the achievement of learning competencies. Previous studies have shown that PBL has a positive impact on cognitive, affective, and psychomotor domains, positioning it as a relevant strategy for addressing the educational challenges of the 21st century. This study employed an experimental method using a Nonequivalent Control Group Design, involving Grade X students at SMA Negeri 2 Salatiga. Class X-A served as the control group, while class X-B was designated as the experimental group. Data collection was carried out through pre-tests and post-tests, followed by statistical analyses including tests for normality, homogeneity, and mean differences. The results demonstrated that the use of different instructional media with the same teaching model led to higher post-test scores in the experimental group (72.44) compared to the control group (69.90). The t-test result of 2.072 exceeded the t-table value of 1.995, with a significance level of 0.004 < 0.05. These findings indicate that the PBL model supported by Google Sites effectively enhances learning outcomes. In conclusion, the integration of PBL and Google Sites improves student performance, particularly in topics related to payment systems and financial instruments. The scientific contribution of this research lies in its innovative integration of problem-based learning with the digital platform Google Sites, which has been scarcely explored in similar studies. This study provides empirical evidence that simple yet interactive digital tools can strengthen the effectiveness of PBL in the context of economics education, especially when dealing with abstract and theoretical subjects such as payment systems. Moreover, the findings present new opportunities for educators and curriculum developers to explore accessible and practical technology-enhanced learning strategies that do not require complex infrastructure. Thus, this study not only enriches the literature on the effectiveness of PBL but also offers practical and applicable solutions for improving educational quality in the digital era